PENGARUH KONSERVATISME AKUNTANSI, CAPITAL INTENSITY, DAN INVESTMENT OPPORTUNITY SET PADA TAX AVOIDANCE - Dewi, Desi Kusuma; Noviari, Naniek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Tax avoidance is one way to avoid taxes legally that does not violate tax regulations. Tax avoidance can be said to be a complicated and unique issue because on one hand it is permissible, but on the other hand it is undesirable. Although it does not violate tax regulations, these actions are basically not in accordance with tax laws and make state tax revenues not optimal. This study aims to determine the effect of accounting conservatism, capital intensity, and investment opportunity set on tax avoidance. The population of this study focuses on mining companies on the Indonesia Stock Exchange for the 2016-2019 period, with total of 47 companies. The number of companies that were selected as samples were 11 companies, hence 44 observations were obtained during the study period. The analysis technique used in this research is multiple linear regression. The results of the analysis shows accounting conservatism has no effect on tax avoidance, capital intensity has a positive effect on tax avoidance, and the investment opportunity set has a negative effect on tax avoidance. This shows accounting conservatism is not a causal variable that influence companies to carry out tax avoidance and the higher the capital intensity of the company, the higher the tax avoidance action taken by the company and the higher the investment opportunity set of the company, the lower the tax avoidance action taken by the company.